2014
DOI: 10.1038/jcbfm.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Labeled Annexin A5 is not Suited for SPECT Imaging of Brain Cell Death in Experimental Murine Stroke

Abstract: Cell death is one of the pathophysiological hallmarks after stroke. Markers to image cell death pathways in vivo are highly desirable. We previously showed that fluorescently labeled Annexin A5 (AnxA5), which binds specifically to phosphatidylserine (PS) on dead/ dying cells, can be used in experimental stroke for monitoring cell death with optical imaging. Here we investigated whether dual-labeled AnxA5 (technetium and fluorescence label) can be used for single-photon emission computed tomography (SPECT) of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Hematoxylin/eosin staining of kidney histology slices from probe-treated rats did not show any abnormalities (Figure S11), suggesting that the kidney retention was not due to probe-induced cell death. A similar kidney retention effect has been observed with Annexin V, 44,45 where there is histological evidence that Annexin V localizes to the distal tubular cells in healthy kidneys 46,47 due to relatively high levels of PS in the cortical regions of the kidney. 48 The favorable biodistribution profile of fluorescent probe 1 prompted us to conduct a comparative study of two radiotracer probes, 9 and 10 (Scheme 4).…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…Hematoxylin/eosin staining of kidney histology slices from probe-treated rats did not show any abnormalities (Figure S11), suggesting that the kidney retention was not due to probe-induced cell death. A similar kidney retention effect has been observed with Annexin V, 44,45 where there is histological evidence that Annexin V localizes to the distal tubular cells in healthy kidneys 46,47 due to relatively high levels of PS in the cortical regions of the kidney. 48 The favorable biodistribution profile of fluorescent probe 1 prompted us to conduct a comparative study of two radiotracer probes, 9 and 10 (Scheme 4).…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…26,27 In vivo experiments showed that 99m Tc-Anx-V128 may be superior than 99m Tc-Annexin V-HYNIC which has a high uptake in kidneys and the liver, that might be limiting to an acceptable target to background ratio, 28 and to HIS-cys-Anx-AF568 which was too hydrophilic to reach the cerebral compartment. 29…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, 99m TC radiolabeled AnxA5 and AnxA5-conjugated gold nanoparticles were valuable diagnostic imaging tools in mouse models for atherosclerosis [ 253 , 254 , 255 ] ( Table 5 d). AnxA5 dual-labeled with 99m TC and Alexa Fluor 568 allowed detection of ethanol-induced cell death in the femur muscle but failed to visualize cell death in a murine model for stroke [ 272 ]. Imaging of apoptosis using 111 In- and DOTA-peptide -labeled AnxA5 monitored efficacy of suicide gene therapy after treatment with ganciclovir in NG4TL4 sarcoma expressing herpes simplex virus thymidine kinase [ 273 ].…”
Section: Anxa5mentioning
confidence: 99%